DEMOCRACY, COMMUNALISM AND VIGILANTISM: An Analytical Study of Indian Democracy in Reference to Rajadharma in the Manusmrti - Chundamthadam, Stephen (Asian Horizons, 2017)
The public beating and humiliation of dalits, in Una, Gujarat, lynching of Muslims in the name of cow protection, exploitation and killing of dalits and tribals in different parts of the country reveal the failure of the democratically elected government’s responsibility to ensure law and order in the country. Repeated incidents of cow vigilantism, supported by the government and the powerful, reflect the mind of the ruling minority and the indifference of the general public. It is more disheartening that people who are in authority betray the trust of the common people by supporting such atrocities. For the effective functioning of a democracy, people in all the three units i.e., legislature, judiciary and executive have to consider the state’s interest as their own work as if they are the servants of the people. But now in Indian democracy legislatures are busy enacting laws to suit their interest; similarly many in the Judiciary and the executive are not able to transcend their narrow selfish interest for the sake of the larger good. As a result of the irresponsible and selfish administration by those who are in authority like the incompetent steersman of the ship in Plato’s republic, justice is refused to the poor and the ordinary people. Such an irresponsible situation in the country calls forth involvement by the masses. People are forced to take law into their hands and enforce justice for the helpless. This article is an analytical study of democracy in India in the context of Vigilantism, lynching, exploitation of tribals and dalits and communal violence.